Rancang Bangun Sistem Penentuan Jalur Evakuasi Keluar Gedung Rumah Sakit Saat Kondisi Darurat Menggunakan Algoritma Dijkstra Dengan Antrian Prioritas - Kemala, Ade Putera; Ichwana, Dody (Universitas Andalas, 2019)
Disaster is a sudden event, such as an accident or a natural catastrophe, that causes great damage or loss of life. Disasters can occur at any time, therefore a mechanism is needed to evacuate out of the building during a disaster. Generally public facilities have provided instructions and evacuation routes outside the building. Based on the severity of the disaster and the evacuation capability of the victim, the evacuation strategy can range from evacuation as soon as possible, evacuate slowly, move to a safe location inside the building or take refuge in the available protection room and wait for the rescue team to arrive. The algorithm for finding the shortest paths can be used to determine the evacuation route. But this path is still static, if the route damaged in then the evacuation route would become useless. The time for the evacuation process can also increase if the condition of the evacuation route is not known whether damaged or not. The solution to solve this problem is to make a system that can help find the safest and shortest evacuation routes during emergencies. This system consist of microcontroller Arduino Mega to control the system and led for evacuation sign. The evacuation routes is determined by implementing dijkstra algorithm with priority queue to search the shortest path.